Study UV-Visible and FTIR Characterization of ZnPc Dye using Double Solvent - Ban Mazin Alshabander (Journal of Global Pharma Technology, 2020)
The effects of dissolving zinc phthalocyanine (ZnPc) in two solvents, (N, N-dimethylformamide (DMF)/water, dimethylsulphoxide (DMSO)/water, tetrahydrofuran (THF)/water), on the absorption spectra and infrared spectra were studied using (UV–Vis) spectroscopy and FTIR spectrophotometer. Solvents affected on the photochemical and photophysical properties of ZnPc complexes. The noticed trend inside the difference of Q-band position with solvent was occasionally attributed to solvent parameters comprising aromaticity, arrange power, polarity, and refractive index. UV-V spectra analysis showed non-proof of aggregation in sol as a display throught great unperturbed phthelocyanine Q band. zinc phthalocyanine emerge absorption spectra with duo essential band electron the Q band with a generality (685, 675 and 680) nm separately as well as Soret B band with an extreme of (340, 340 and 350) nm separately. Farthest potential aggregation included method is such the H-aggregation because of rise shift energy of absorption spectrum as well as provided information via the potential electrostatic allocation onto molecule zinc phthalocyanine . FTIR results showed that elevate include peaks belongs to ZnPc with the alteration in the present of the two solvent furthermore little shift toward low energy existed. Keyword: Double solvent, Metal-Phthalocyanine dye, Energy bandgap.